Implementation of the Problem-Based Learning Model to Enhance Critical Thinking Skills of Elementary School Students: A Literature Review - Heri Sumadi (UM Purwokerto Press, 2025)
The rapid development of the Industrial Revolution 4.0 era demands that students possess 21st-century skills, including critical thinking, problem-solving, creativity, communication, and collaboration. However, science learning in schools still faces challenges in equipping students with these skills. Teachers need to act as facilitators capable of implementing innovative learning to enhance students' 21st-century skills in science. One proposed solution is through the problem-based learning model. The problem-based learning model can be an alternative to make students the center of learning. Problem-based learning encourages students to learn independently and collaborate in solving real-world problems. This research aims to develop students' critical thinking skills in science through the implementation of the problem-based learning model, motivated by the low level of these skills. This research employs a literature study, a data collection method from various sources such as journals and books through Google Scholar searches. The collected data were analyzed through selection, comparison, integration, and filtering. The results of the research indicate that understanding and optimizing the problem-based learning model can address the problems of its implementation in elementary schools, thereby potentially improving students' critical thinking skills in science learning.